2006
DOI: 10.1002/ceat.200500320
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrodimerization of Isobutene to 2,5‐Dimethyl‐1,5‐Hexadiene over Bismuth‐(III)‐Oxide and Various Additives

Abstract: ) have been chosen to study the oxidative dehydrodimerization of isobutene. The catalytic performances were investigated by variation of the residence time, isobutene to oxygen molar ratio, and pressure. The best results for 2,5-dimethyl-1,5-hexadiene (DMH) yield (13 %) were achieved with Bi 2 O 3 as the catalyst. The selectivity of DMH reaches values of over 90 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Taubert et al [18] studied the oxidative dehydrodimerization of isobutene using Bi 2 O 3 and mixtures with different additives (Cr 2 O 3 , MoO 3 , NH 4 VO 3 , SnO 2 , and V 2 O 5 ). They observed that the highest yields of 2,5-dimethyl-1,5-hexadiene yield were achieved with Bi 2 O 3 as the catalyst and selectivities over 90% were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Taubert et al [18] studied the oxidative dehydrodimerization of isobutene using Bi 2 O 3 and mixtures with different additives (Cr 2 O 3 , MoO 3 , NH 4 VO 3 , SnO 2 , and V 2 O 5 ). They observed that the highest yields of 2,5-dimethyl-1,5-hexadiene yield were achieved with Bi 2 O 3 as the catalyst and selectivities over 90% were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Taubert et al developed a Bi 2 O 3 catalyst for the oxidative dimerization of isobutene in the presence of oxygen. 11 The Bi 2 O 3 catalyst provided a 13% yield of 2,5-DMH with 53% selectivity. Because the oxidation of isobutene produced carbon monoxide and carbon dioxide, the catalyst demonstrated less selective performance by increasing the isobutene conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the terminal activation of isobutene is not expected in conventional carbocation reactions because of the high stability of tertiary cations. 2,11 In contrast, the radical reactions can activate the terminal carbon in isobutene because of the high chain reactivity between the radicals and the nonradical species. [12][13][14] Conventionally, azo compounds and organic peroxides such as azo-bis isobutyronitrile (AIBN) [15][16][17] and tert-butyl hydroperoxide, [18][19][20] are used as radical initiators.…”
Section: Introductionmentioning
confidence: 99%